Procrastination and the non‐monotonic effect of deadlines on task completion. (2nd November 2021) - Knowles, Stephen; Servátka, Maroš; Sullivan, Trudy; Genç, Murat
Abstract: We conduct a field experiment to test the non‐monotonic effect of deadline length on task completion. Participants are invited to complete an online survey in which a donation goes to charity. They are given either 1 week, 1 month, or no deadline to respond. Responses are lowest for the 1‐month deadline and highest when no deadline is specified. No deadline and the 1‐week deadline feature a large number of early responses, while providing a 1‐month deadline appears to give people permission to procrastinate. If they are inattentive, they might forget to complete the task.